The Challenges of Mask Wearing Among USIM Medical Students during the Pandemic of COVID-19 - Raja Hassrullah Raja Hussin; Amirah Roslan; Nur Faizatul Murni Mokhtar; Nurin Alia Abdul Manaf; Najat Ruhi Ahmad Sa’aduddin; Nuur Nabilah Balqis Wan Abdullah; Wan Shahida Wan Sulaiman; Noradilah Samseh Abdullah (USIM Press, 2024)
ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences (Special Issue IHEC 01-2021) [April 2021]